Smoking behavior of adolescents and their view towards government's ban on smoking in public places in Kathmandu - Dahal, S; Subedi, RK; Maharjan, S; Maharjan, J (Nepal Journal of Medical Sciences, 2015)
Background: Several studies have reported that different forms of tobacco use are high in Nepal. However, information about factors affecting the cigarette smoking behavior of adolescents is inadequate. The objective of this study was to explore the cigarette smoking behavior of adolescents and to determine its association with their views towards cigarette smoking. Methods: A cross-sectional study was conducted among 394 adolescent students by using questionnaire method in 3 randomly selected colleges of Kathmandu district, Nepal. Data were analyzed by using bivariate and binary logistic regression analysis. Results: The study found that 22% of the students were ever smokers. Higher percentage of students receiving more amount of pocket money, having poor academic performance, having frequent dispute with teachers, having alcohol using and smoker family members were ever smokers. Multivariate analysis showed that students were more likely to be current smokers if they have positive views towards smoking and were less likely to be current smokers if they have negative view towards smoking (p<0.01). Conclusion: Reasons for smoking are many that create challenges for smoking control programs. Changing the views and imagery of adolescents’ towards cigarette smoking should also be considered while designing such programs. Nepal Journal of Medical Sciences Vol.3(2) 2014: 94-100